Estado nutricional e ingestão de macronutrientes de pacientes com hepatite crônica pelos vírus B ou C - Penélope Lacrisio dos Reis Menta (2013)
INTRODUCTION/AIMS: Nutritional disorders are cofactors to progression of liver fibrosis and comorbidities in patients with chronic viral hepatitis B or C. We investigated the nutritional status and macronutrient intake these patients. METHODS: 230 patients with hepatitis B (n=80) or C (n=150) were evaluated by subjective global assessment (SGA), anthropometric measurements and 24- hour recall. The risk of metabolic complications was assessed by the waist circumference (WC) and percentages of body fat (%BF). Alcohol abuse was considered above 20g and 30g daily for women and men, respectively. RESULTS: Mean age 54 years, 52.6% female, 75% no cirrhotic and 15% cirrhotic. By SGA, 86.5% were nourished and 13.5% malnourished. Malnutrition was associated with cirrhosis (PR=1.25, 95% CI 1.1 to 1.4, p<0,001), alcohol abuse, direct bilirubin>3,0mg/dL, INR>1,1, platelets<150x103/mm3, hemoglobin<12g/dL and albumin<3,5g/dL (p<0.05). By BMI, 43.9% patients were eutrophic, 33.5% overweight, 21.3% obese and 1.3% underweight. Obese had higher prevalence of steatosis than eutrophic (PR=1.53, 95%CI=1.15 - 2.04, p=0.003) and overweight (PR=1.71, 95% CI 1.33 to 2.20, p<0.001). O verweight/obesity was associated with WC>94cm (men) and 80cm (women), %BF>25% (men) and 32% (women) (p<0.01), triglycerides>150mg/dL, HDL-c<40mg/dL, glucose>99mg/dL, insulin >20 U/mL, RI-HOMA>3.2 and TSH>2.5 U/mL (p<0,05). Most patients had high consume of saturated fat and carbohydrate and low consume of fiber, total fat and protein intake. CONCLUSIONS: Overweight, obesity and inadequacies in macronutrient intake are frequent patients with viral hepatitis B or C. Malnutrition is associated with cirrhosis and obesity with steatosis. Several nutritional corrective actions are needed in clinical practice.